2014
DOI: 10.1002/chem.201405316
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexes of a Boron‐Dipyrromethene (BODIPY)‐Tagged N‐Heterocyclic Carbene (NHC) as Luminescent Carbon Monoxide Chemodosimeters

Abstract: Several metal complexes with a boron dipyrromethene (BODIPY)-functionalized N-heterocyclic carbene (NHC) ligand 4 were synthesized. The fluorescence in [(4)(SIMes)RuCl2(ind)] complex is quenched (Φ = 0.003), it is weak in [(4)PdI2(Clpy)] (Φ = 0.033), and strong in [(4)AuI] (Φ = 0.70). The BODIPY-tagged complexes can experience pronounced changes in the brightness of the fluorophore upon ligand-exchange and ligand-dissociation reactions. Complexes [(4)MX(1,5-cyclooctadiene)] (M = Rh, Ir; X = Cl, I; Φ = 0.008-0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 59 publications
1
64
2
Order By: Relevance
“…[12,13] The azolium salts used for the synthesis of complexes 2, 3,a nd 5 were prepared in good yields using the respectiveb dp(CH 2 ) 5 Br ands uitable imidazoles (Scheme 3). [12,13] The azolium salts used for the synthesis of complexes 2, 3,a nd 5 were prepared in good yields using the respectiveb dp(CH 2 ) 5 Br ands uitable imidazoles (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[12,13] The azolium salts used for the synthesis of complexes 2, 3,a nd 5 were prepared in good yields using the respectiveb dp(CH 2 ) 5 Br ands uitable imidazoles (Scheme 3). [12,13] The azolium salts used for the synthesis of complexes 2, 3,a nd 5 were prepared in good yields using the respectiveb dp(CH 2 ) 5 Br ands uitable imidazoles (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…[12,13] The azolium salts used for the synthesis of complexes 2, 3,a nd 5 were prepared in good yields using the respectiveb dp(CH 2 ) 5 Br ands uitable imidazoles (Scheme 3). [12] Complexes 2, 3,a nd 5 were synthesized from the respective azolium salt and [AuCl(Me 2 S)] in as ingle step, following ag eneral procedure for the synthesis of [(NHC)AuCl] complexes. It is likely,t hat the steric bulk of the BODIPY unit hampers the nucleophilic substitution reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, two such molecular probes were developed, which rely on palladium‐catalyzed fluorogenic reactions involving CO (Scheme , middle) . We recently demonstrated that the exchange of a cod ligand in an Ir complex by two CO molecules leads to a pronounced increase in the fluorescence intensity, suitable for CO detection (Scheme , bottom) . However, our previous probe, like most bodipy's, suffers from a small Stokes shift.…”
Section: Introductionmentioning
confidence: 92%